Board of directors capabilities and accountability disclosure practice of Malaysian non-profit organisations / Mohd Hisham Mahamud - Mahamud, Mohd Hisham (2022)
The Board of directors (BODs) capabilities and the accountability disclosure practice or the relationships between the two emerge as areas of interest, warranting a new or renewed prescription to match the changed NPO's world. In order to investigate the issue, the research formulates four significant objectives; to analyse the patterns and motivations underlying the NPOs accountability disclosure practice; to propose the desirable BODs capabilities, to examine the relationship between BODs capabilities and accountability disclosure practice and to investigate whether the presence of BODs diversity moderates the interaction between BODs human capital capability and the accountability disclosure practice. To address the objectives, the research was drawn from the resource-based view and signalling theories. It examined accountability disclosure practise using a comprehensive framework, a systematic approach to identifying and finalising desirable BOD capabilities, and NPO disclosures as sources of accountability evidence. The population for the research is NPOs registered as Companies Limited by Guarantee under Suruhanjaya Syarikat Malaysia. The research then adopts a quantitative approach to capture the quality and quantity of the accountability disclosure practice information in the disclosures of 103 NPOs using the accountability disclosure index for three consecutive years (2014 to 2016). It is observed that the accountability disclosure practice improve yearly, albeit imbalanced, varying substantially, selective, inconsistent, and resembling the corporate sectors which are rendered by issues of interest, importance, legitimacy and concern to stakeholders. The research also proposes 13 desirable BODs capabilities for the Malaysian NPOs. Based on the literature, these 13 capabilities have been justified and expounded. Subsequently, findings also reveal that only BODs human capital capability and NPOs profitability demonstrate a decently significant influence on the quality and quantity of the accountability disclosure practice for three consecutive years. Specifically, some observations were made as a result of the multiple linear regressions, such as lack of support for hypotheses tested, inconsistencies in the research findings, inverse relationships instead of expected positive relationships and collective or subgroup measurement of BODs capabilities. The findings suggest that the literature on the accountability disclosure practice by NPOs in Malaysia is still in its early stages and that the lack of a specific reporting framework, sample size and period could explain the above findings. The research embarks on a successful deliberation to prove that BODs expertise diversity is the only moderating variable that contributes in a meaningful way to the interaction between BODs human capital capability and the accountability disclosure practice. Overall, the results refiect the economic motivation of NPOs to ensure the relevance of the information for economic benefit and the social motivation to maximise trust and support. This research's findings will redound to society's benefit, a valuable reference for relevant parties and the basis for further research and avenues for different methodology. Specifically, this research enhances the understanding of the current state of accountability disclosure practice by NPOs in Malaysia by providing the basis for empirical research on BODs capabilities, implications for BODs practices and BODs evaluation, and evidencing the relationship between BODs capabilities and accountability disclosure practice in terms of quality and quantity measurement.